(untitled) (American Journal of Language, Literacy and Learning in STEM Education (2993-2769), 2025)
The article is dedicated to the description of prepositional phrases using the modeling method, which allows for the systematization of data and the identification of patterns in their structure and usage. The study examines the process of creating abstract models for analyzing prepositions and their combinations with nouns, pronouns, and numerals. Several stages of modeling are considered, including data collection and classification, identification of interaction models, and programmatic modeling for automating analysis. The modeling method not only systematizes knowledge about prepositional phrases but also reveals hidden connections between different types of constructions. The article also analyzes the functions of prepositional constructions in language, such as expressing location, time, cause, purpose, and means of action. The results presented demonstrate the effectiveness of the modeling method in both syntactic and semantic language analysis.